2021
DOI: 10.1111/fwb.13689
|View full text |Cite
|
Sign up to set email alerts
|

Environmental drivers of cladoceran assemblages at a continental scale: A synthesis of Alaskan and Canadian datasets

Abstract: Cladocera serve as important bio‐ and paleo‐indicators of lake food webs and environmental conditions. The ecological optima of cladocerans are often established by regional‐scale calibration sets, with subsequent comparisons to limnological variables. However, due to logistical constraints when sampling large numbers of lakes, this approach often limits the length of the environmental gradients that can be examined. To extend spatial and limnological gradients, we combined 20 datasets (388 lakes) containing b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 124 publications
(136 reference statements)
1
8
0
Order By: Relevance
“…Lake depth and pH were identified as major environmental drivers in our study, which echoes observations reported by Labaj et al. (2021) for cladoceran assemblages in surface sediments from 388 lakes across Canada and Alaska. Our RDA analyses identified lake depth as a key factor influencing cladoceran composition in all three sample types in the all‐species data set.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Lake depth and pH were identified as major environmental drivers in our study, which echoes observations reported by Labaj et al. (2021) for cladoceran assemblages in surface sediments from 388 lakes across Canada and Alaska. Our RDA analyses identified lake depth as a key factor influencing cladoceran composition in all three sample types in the all‐species data set.…”
Section: Discussionsupporting
confidence: 92%
“…Across all sample types (water column, contemporary (top) sediments and pre‐industrial (bottom) sediments), we identified 51 cladoceran taxa in the 85 study lakes (see Table S2 for the full list of taxa; Figure 3 for summary). Similarly, 51 cladoceran taxa were identified in a synthesis study across Alaskan and Canadian lakes (Labaj et al., 2021), while total richness was of 53 taxa in the larger 101 LakePulse lake dataset where subfossil cladocerans were enumerated (Paquette, Griffiths, et al., 2022). Across our 85 lakes, 16 taxa were common to all three sample types, 33 were common to both sediment samples, one taxon was uniquely shared between the water column and the top sediment sample, and one taxon was found only in the bottom sediment sample.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…The species‐specific effects of calcium and pH that we detected in our experiment were generally in agreement with long‐term changes across the Killarney lakescape (Table 3), suggesting that declining calcium concentrations are likely to affect zooplankton communities in acid‐recovering lakes. While the co‐gradient of pH and calcium is the primary environmental driver of cladoceran assemblages in northern regions of continental North America (Labaj et al, 2021), it is likely that regional variation in abiotic conditions and food web structure will also modulate zooplankton responses. For example, in historically acidified Adirondack lakes (New York, USA), the effect of declining calcium on zooplankton was modified by changes in lake “browning”/dissolved organic carbon concentrations (Leach et al, 2019).…”
Section: Discussionmentioning
confidence: 99%